2022
DOI: 10.1111/php.13680
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Blue/Carbon Dots Composite with Photothermal and Photodynamic Properties: Synthesis, Characterization, and Antibacterial Application

Abstract: Photodynamic therapy and photothermal therapy provide new ways to combat antibiotic resistance. In this research, methylene blue (MB) as an effective photosensitizer was conjugated with carbon quantum dots (CQDs), the composite product not only possessed good antibacterial properties against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) due to excellent singlet oxygen (1O2) production rate and light heat transfer performance, but also showed good biocompatibility. Combined with 808 nm and 66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The surface chemical bond composition was characterized by FTIR spectroscopy (Figure i). MB-CPDs showed stretching vibrations of C–H and N–H (3414 cm –1 ), O–H (2925 cm –1 ), CO (1731 cm –1 ), CC (1599 cm –1 ), C–N (1385 cm –1 ), CN (1250 cm –1 ), and C–S (1138 cm –1 ), which were consistent with those of MB. , Of note, it can be seen from the FITR spectra that MB-CPDs contained more oxygen-containing functional groups (−OH and CO) than MB. Taken together, these results demonstrated that the functional groups of the raw material photosensitizer were retained in PS-CPDs, which are expected to play a critical role in Aβ photooxygenation by the generated ROS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The surface chemical bond composition was characterized by FTIR spectroscopy (Figure i). MB-CPDs showed stretching vibrations of C–H and N–H (3414 cm –1 ), O–H (2925 cm –1 ), CO (1731 cm –1 ), CC (1599 cm –1 ), C–N (1385 cm –1 ), CN (1250 cm –1 ), and C–S (1138 cm –1 ), which were consistent with those of MB. , Of note, it can be seen from the FITR spectra that MB-CPDs contained more oxygen-containing functional groups (−OH and CO) than MB. Taken together, these results demonstrated that the functional groups of the raw material photosensitizer were retained in PS-CPDs, which are expected to play a critical role in Aβ photooxygenation by the generated ROS.…”
Section: Resultsmentioning
confidence: 99%
“…PDT exerts its therapeutic effect mainly by photoactivating photosensitizer (PS) to generate ROS, including OH·, 1 O 2 , and O 2 – . , Phenothiazine dyes possess broad red light absorption (630–680 nm) and good photodynamic activity, making them excellent photosensitive materials . Among various phenothiazine dyes, methylene blue (MB) shows great potential in AD therapy due to its high solubility and BBB penetration capability .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The photothermal process also enhances the ROS generation as the local temperature increase resulting in increased permeability of the bacterial cell wall, which further aids in bacterial cell death ( Wen et al, 2022 ). In a series of reports, heteroatom-doped CDs with excellent fluorescence emission were hybridized with curcumin ( Figure 1C ), and methylene blue as common photosensitizers (PS), which enhanced of the ROS generation, water solubility of the applied PS, and the photothermal heat generation for bacterial inactivation ( Yan et al, 2021 ; Lv et al, 2022 ; Wen et al, 2022 ). Similarly, Wen et al, demonstrated that CDs modified with quaternary ammonium salt can simultaneously provide photothermal antibacterial activity and wound healing without any inflammatory damage to surrounding tissues ( Chu et al, 2022 ).…”
Section: Photothermal Applicationsmentioning
confidence: 99%